Salivary Cortisol, Perceived Stress, and Metabolic Syndrome: A Matched Case-Control Study in Female Shift Workers - Garcez, Anderson; Weiderpass, Elisabete; Canuto, Raquel; Lecke, Sheila Bünecker; Spritzer, Poli Mara; Pattussi, Marcos Pascoal; Olinto, Maria Teresa Anselmo (Hormone and Metabolic Research, 2017)
Although the pathogenesis of metabolic syndrome (MetS) is complex and multifactorial, there is limited information if psychological factors, such as stress exposure, are involved in the etiology of MetS. Therefore, this study investigated the associations between MetS and cortisol levels and perceived stress levels among women shift workers in Southern Brazil. A matched case-control study was conducted, including 50 cases of MetS and 200 age-matched controls (±3 years, 4 for each case). Salivary cortisol levels were evaluated immediately after waking and one upon returning home from work. Perceived stress levels were measured by the Perceived Stress Scale with 10 items (PSS-10). Multivariate-adjusted associations between MetS and salivary cortisol levels and perceived stress levels were assessed by conditional logistic regression. Means±standard deviations of salivary cortisol levels were not signiﬁcantly different between cases and controls either immediately after waking (5.37±4.10 vs. 6.03±5.39 nmol/l; p = 0.53) or after work (2.74±2.87 vs. 2.78±2.85 nmol/l; p = 0.93). There was no significant difference in perceived stress level between cases and controls (14.2±5.9 vs. 15.5±5.6; p = 0.15). No independent association was observed in the multivariate model between MetS and salivary cortisol level or perceived stress level after these exposures were stratified into tertiles. Overall, there was no difference between women with or without MetS in regard to the free salivary cortisol and perceived stress. Our results do not support an association between stress exposure and MetS among women shift workers.
Keywords: cortisol; saliva; perceived stress; metabolic syndrome; women; shift work